2011
DOI: 10.1121/1.3518760
|View full text |Cite
|
Sign up to set email alerts
|

The performance of different synthesis signals in acoustic models of cochlear implants

Abstract: Synthesis (carrier) signals in acoustic models embody assumptions about perception of auditory electric stimulation. This study compared speech intelligibility of consonants and vowels processed through a set of nine acoustic models that used Spectral Peak (SPEAK) and Advanced Combination Encoder (ACE)-like speech processing, using synthesis signals which were representative of signals used previously in acoustic models as well as two new ones. Performance of the synthesis signals was determined in terms of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Three different types of sounds were presented in the experiments as described next and illustrated in Figure S2B. These signals were chosen because the findings of previous studies suggested they were likely to be perceived as similar to constant-rate stimulation on one electrode [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different types of sounds were presented in the experiments as described next and illustrated in Figure S2B. These signals were chosen because the findings of previous studies suggested they were likely to be perceived as similar to constant-rate stimulation on one electrode [8].…”
Section: Methodsmentioning
confidence: 99%
“…Noise-band carriers are the most commonly used because they seem to provide the most accurate simulation for speech intelligibility modeling [7]. However, some researchers have found that existing simulators are not always accurate models of phoneme perception [8], and they may not reproduce exactly the sound perceived by CI users [7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a simpler model, Bonham and Litvak (2008) also argued that BP should produce a broader spread than MP when the two peaks are considered. Two previous vocoder studies (Bingabr et al, 2008;Strydom and Hanekom, 2011b) that simulated the excitation spreads of MP and BP partly based their choice of filter bandwidth on saline tank measurements reported by Kral et al (1998). In both cases, the choice of the BP bandwidth was based on measurements corresponding to a single peak of the BP pattern.…”
Section: Spatial Selectivity Of Mp and Bp Configurationsmentioning
confidence: 99%
“…However, insuring correspondence between vocoder simulations and actual implant performance remains difficult. Strydom and Hanekom (2011) compared the performance of a tone vocoder (resembling the one used here) and eight other vocoder models on consonant and vowel recognition tasks with performance measured for Nucleus CI users with SPEAK or ACE speech processors (Pretorius et al, 2006). Although each vocoder emulated some aspects of CI listening well, none were able to closely approximate all aspects of CI listening.…”
Section: Limitations Of Tone Vocoder Simulationsmentioning
confidence: 98%